Informal Seed systems and the management of gene flow in traditional agroecosystems: the case of cassava in Cauca, Colombia - Dyer, George; González, Carolina; Lopera, Diana Carolina (2012)
Our ability to manage gene flow within traditional agroecosystems and their repercussions requires understanding the biology of crops, including farming practices" role in crop ecology. That these practices" effects on crop population genetics have not been quantified bespeaks lack of an appropriate analytical framework. We use a model that construes seed-management practices as part of a crop"s demography to describe the dynamics of cassava (Manihot esculenta Crantz) in Cauca, Colombia. We quantify several management practices for cassava the first estimates of their kind for a vegetatively-propagated crop describe their demographic repercussions, and compare them to those of maize, a sexually-reproduced grain crop. We discuss the implications for gene flow, the conservation of cassava diversity, and the biosafety of vegetatively-propagated crops in centers of diversity. Cassava populations are surprisingly open and dynamic: farmers exchange germplasm across localities, particularly improved varieties, and distribute it among neighbors at extremely high rates vis-à-vis maize. This implies that a large portion of cassava populations consists of non-local germplasm, often grown in mixed stands with local varieties. Gene flow from this germplasm into local seed banks and gene pools via pollen has been documented, but its extent remains uncertain. In sum, cassava"s biology and vegetative propagation might facilitate pre-release confinement of genetically-modified varieties, as expected, but simultaneously contribute to their diffusion across traditional agroecosystems if released. Genetically-modified cassava is unlikely to displace landraces or compromise their diversity, but rapid diffusion of improved germplasm and subsequent incorporation into cassava landraces, seed banks or wild populations could obstruct the tracking and eradication of deleterious transgenes. Attempts to regulate traditional farming practices to reduce the risks could compromise cassava populations" adaptive potential and ultimately prove ineffectual.